Enhanced antimicrobial, antibiofilm and ecotoxic activities of nanoencapsulated carvacrol and thymol as compared to their free counterparts. (January 2023) - Yammine, Jina; Gharsallaoui, Adem; Fadel, Alexandre; Mechmechani, Samah; Karam, Layal; Ismail, Ali; Chihib, Nour-Eddine
Abstract: Essential oils active components emerged as captivating antimicrobials to control biofilms developed on food contact surfaces. Free and nanoencapsulated carvacrol (CAR) and thymol (THY) were assessed as antimicrobials against Salmonella Enteritidis biofilms adhered to stainless steel. The developed spherical nanocapsules using the spray-drying technique showed an average size ranged between 159.25 and 234.76 nm and zeta potential values ranged between 23.60 and 24.66 mV. The minimal inhibitory concentrations (MIC) of free THY and CAR were both 1.25 mg L −1 . Nanoencapsulation reduced MIC values to 0.62 mg L −1 (THY) and 0.31 mg L −1 (CAR). Furthermore, the exposure to free and nanoencapsulated CAR and THY induced a destabilization of bacterial membranes with obvisous morphological deformations and a pronounced leakage of potassium ions and green fluorescent proteins. Eradication of S. Enteritidis biofilms developed on stainless steel was achieved following a 15 min treatment with nanoencapsulated CAR and THY at 2 MIC. Free antimicrobial exposures induced up to 4.27 log CFU cm −2 reductions. Additionally, the ecotoxicity tests against Daphnia magna crustaceans reported a non-toxicity of both free and nanoencapsulated CAR and THY after 48 h exposure. Thereby, both CAR and THY antimicrobials proved to be promising natural surface disinfectants that require further exploration and incorporation in food industries. Highlights: Nanoencapsulation promoted the antibacterial activity of free terpenes. A total eradication of Salmonella Enteritidis biofilms was achieved. Nanoencapsulation reduced the ecotoxic effect against Daphnia magna crustaceans.